1251. Contaminated Sinks May be an Environmental Source for Serial Transmission of Carbapenem-Resistant Enterobacteriaceae (CRE) to ICU Patients. (26th November 2018) - Lewis, Sarah S; Seidelman, Jessica; Huslage, Kirk; Carriker, Charlene; Hnat, Amy; Lobaugh-Jin, Erica; Sova, Christopher; Taylor, Bonnie; Strittholt, Nancy; Vereen, Sheila; Willis, Robbie; Campbell, Christy; et al.
Abstract: Background: We performed an investigation after noting an increase in hospital-onset (HO) KPC-producing Enterobacteriaceae (KPC-E) infections in patients admitted to a tertiary referral hospital in North Carolina. Methods: We defined pre-outbreak (January 1, 2017–June 30, 2017), outbreak (July 1, 2017–October 31, 2017), and post-outbreak (November 1, 2017–March 31, 2018) phases. A clinical case was defined as any positive clinical culture for KPC-E. HO was defined as a positive clinical or surveillance culture collected on hospital day ≥3. Patients were mapped in space and time to inform targeted environmental sampling. Whole-genome sequencing (WGS) was performed on selected KPC K. pneumoniae environmental and patient isolates to determine relatedness. In October 2017, a CRE prevention bundle was implemented that included daily communication of CRE patient movement, increased audits/feedback of HCW compliance with hand hygiene, enhanced cleaning and disinfection in CRE rooms and high-risk units with bleach and UVC disinfection, and weekly rectal surveillance screens in four adult ICUs. Results: 0.67 clinical cases of KPC-E per month were observed during the pre-outbreak period compared with 3.75 clinical cases of KPC-E per month during the outbreak period. K. pneumoniae was the most common species (Figure 1). Mapping of patients revealed probable direct and indirect transmission between patients in multiple hospital units (Figure 2). three patients who were non-sequentially admitted to the same ICU room over a 12-week span acquired KPC K. pneumoniae (Figure 2). Environmental cultures from the in-room sink drain and P-trap grew KPC K. pneumoniae that was related to the patient isolates by WGS; the sink was removed. Although no additional clinical cases of KPC-E occurred after full implementation of the bundle and sink removal, we continued to observe acquisition of KPC-E rectal colonization in all four ICUs (Figure 3). Conclusion: We describe a multispecies outbreak of KPC-E that was mitigated through evidence-based CRE control measures and removal of a colonized sink. However, ongoing low-level presumed transmission of KPC points to persistent environmental sources. Additional study is needed to understand the prevalence of CRE in hospital sinks, factors that drive drain colonization, and contribution of CRE in a sink to nosocomial transmission. Disclosures: All authors: No reported disclosures.